An investigation of user perceptions and attitudes towards learning objects - Lau, Siong Hoe; Woods, Peter Charles (BLACKWELL PUBLISHING, 2008)
This study empirically evaluates the technology acceptance model drawn from Information Systems (IS) literature to investigate how user beliefs and attitudes influence learning-object use among higher education learners by evaluating the relationships between perceived usefulness, perceived ease of use, attitude, behavioural intentions and actual use. In the study, 601 potential learning-object users were presented with an introductory demonstration of learning objects for a Digital Systems course. Following the demonstration and practice, data on user beliefs, attitudes and intention to use learning objects were gathered, while data on actual use of learning objects was collected at the end of the semester. Subjects with prior experience using the learning objects were eliminated from further analysis, resulting in a final sample of 481 users. structural equation modelling was employed to test the hypothesised study model. The analysis showed that both the user beliefs and attitudes have significant positive relationships with behavioural intention and that behavioural intention accurately predicted the actual use of learning objects. The results extend the validity of the TAM into a learning object context and clearly pointed out that it can be used to predict users' future behaviour.